Dampak Kepercayaan, Kualitas Pelayanan, dan Citra Merek Terhadap Loyalitas Pengguna Gojek di Kota Serang - Aziz, Abdul; Kurniawanto, Hadi; Gupron, Akhmad; Hanafiah , Hafidz (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Customer loyalty is defined as a deep commitment to making a repeat purchase or recommending a particular product or service even though there are alternative options that may be more appealing. Customer loyalty can be affected by several factors, including trust, quality of service, and brand image. The purpose of this study is to determine the impact of trust, service quality, and brand image simultaneously on the loyalty of Gojek users in Serang City. This study uses a quantitative approach where the sample in this study is 96 respondents who are Gojek customers in Serang City who use Gojek services, using the purposive sampling method. The results of the research on trust variables, service quality, and brand image have a simultaneous significant influence on the loyalty of Gojek users. It is evidenced by the value of F calculated 20.645 > F table 2.70 and a significance value of 0.000 < α (0.05). The coefficient of determination (R Square) shows that 40.2% of customer loyalty valriation can be explained by all three independent variables. Meanwhile, 59.8% were influenced by other variables outside this research model. The conclusion of the results of this study provides that the combination of customer trust, as well as good service quality and strong brand image, plays an important role in increasing the loyalty of Gojek users in Serang City. Gojek needs to continue to improve these aspects in order to maintain and expand its loyal customer base.